Perilaku Asertif, Harga Diri dan Kecenderungan Depresi - Imani Khan, Rosa (Persona:Jurnal Psikologi Indonesia, 2012)
Abstract. This study aimed to find out correlations among assertive behaviors and self-esteem with tendency to depression. The study wasÂ  conducted toward 119 adolescents, with ages 18 to 21 year (last adolescent). Data were collected by scales of assertive behkavior, self-esteem and Beck Depression Inventory (BDI) in indonesian version. Techniques for the data analyses used statistical spearman rank correlation, SPSS for Windows release 13. Results of the analysis found a negative correlation between assertive behavior and tendency to depression. The more assertive behavior,Â  the less tendency to depression, and adversely. Other finding also showed a negative correlation between self-esteem and tendency to depression. The more sel-esteem, the less tendency to depression, and adversely.Keywords: assertive behavior, self-esteem, depression